2014
DOI: 10.7863/ultra.33.8.1393
|View full text |Cite
|
Sign up to set email alerts
|

Increased Epicardial Adipose Tissue Thickness on Transthoracic Echocardiography in Patients With Behçet Disease

Abstract: We found that epicardial adipose tissue thickness was significantly higher and flow-mediated dilatation was significantly lower in patients with Behçet disease than in controls. We suggest that identification of increased epicardial adipose tissue might aid in the diagnosis and treatment of possible coronary artery disease in patients with Behçet disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Carotid intima media thickness, endothelial dysfunction, MPV and EAT thickness are some parameters that suggested for evaluation of increased atherosclerotic risk [3-5,7]. Familial Mediterranean fever is an inflammatory disease suggested to predispose to atherosclerosis [4-6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carotid intima media thickness, endothelial dysfunction, MPV and EAT thickness are some parameters that suggested for evaluation of increased atherosclerotic risk [3-5,7]. Familial Mediterranean fever is an inflammatory disease suggested to predispose to atherosclerosis [4-6].…”
Section: Discussionmentioning
confidence: 99%
“…[7,8,22]. Studies evaluating carotid intima media thickness and endothelial dysfunction in FMF patients have found an increased risk of atherosclerosis [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial adipose tissue appeared as an anechoic space between the epicardial layers on B‐mode images. The epicardial adipose tissue thickness (EATT) was measured as the vertical distance of the space on the free wall of the right ventricle in the parasternal long‐axis view at end diastole …”
Section: Methodsmentioning
confidence: 99%
“…The epicardial adipose tissue thickness (EATT) was measured as the vertical distance of the space on the free wall of the right ventricle in the parasternal long-axis view at end diastole. 11 In the 3DSTE study, a fully sampled matrix-array probe (GE 4V-D) was used to acquire LV full-volume images(frame rate = 25~45 frames/s). These images were stitched in 6 subvolumes in 6 consecutive cycles, including three tomographic orientations at the apex (four-chamber, three-chamber, and two-chamber) and three short-axis sections (basal, middle, and apical).…”
Section: Echocardiography Measurementsmentioning
confidence: 99%
“…Fat tissue developing in the epicardial area is a marker of this systemic response and can function as a lipidstorage depot, as an endocrine organ that secretes hormones, and as inflammatory tissue that secretes cytokines and chemokines (10). Various studies have shown EFT to increase in systemic inflammatory diseases such as RA (6), SLE (7), and Behçet's disease (27). There are very few studies in the literature investigating the association of COPD and EFT.…”
Section: Discussionmentioning
confidence: 99%